2015
DOI: 10.1038/onc.2015.366
|View full text |Cite
|
Sign up to set email alerts
|

SPROUTY-2 represses the epithelial phenotype of colon carcinoma cells via upregulation of ZEB1 mediated by ETS1 and miR-200/miR-150

Abstract: Esta es la versión de autor del artículo publicado en: This is an author produced version of a paper published in:Oncogene 35.23 (2016)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 60 publications
2
42
0
Order By: Relevance
“…MiR-150-5p was revealed to target ZEB1 in various cancers such colon cancer [38], esophageal squamous cancer [37] and ovarian cancer [35], and ZFAS1 was demonstrated to sequestrate miR-150-5p and exerted its pro-metastatic activity in hepatocellular cancer [39]. First, we constructed ZEB1 3’UTR wild type or mutated (predicted miR-150 binding sites) luciferase plasmids in the pmirGLO dual luciferase reporter vector, and luciferase activity was evaluated after co-transfection of miRNA and luciferase plasmids.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…MiR-150-5p was revealed to target ZEB1 in various cancers such colon cancer [38], esophageal squamous cancer [37] and ovarian cancer [35], and ZFAS1 was demonstrated to sequestrate miR-150-5p and exerted its pro-metastatic activity in hepatocellular cancer [39]. First, we constructed ZEB1 3’UTR wild type or mutated (predicted miR-150 binding sites) luciferase plasmids in the pmirGLO dual luciferase reporter vector, and luciferase activity was evaluated after co-transfection of miRNA and luciferase plasmids.…”
Section: Resultsmentioning
confidence: 99%
“…Repression of E-cadherin expression is an important phenotype in EMT, while ZEB1 is a major transcriptional suppressor for E-cadherin via binding to the E-box in the promoter of CDH1 gene directly [54]. Recently, several miRNAs such as miR-200 family and miR-150-5p were confirmed to target ZEB1 and caused mRNA degradation, thus blocking EMT [3538]. As another type of ncRNA, lncRNAs are emerging as important regulators in various biological and disease development processes [2].…”
Section: Discussionmentioning
confidence: 99%
“…25 As mentioned previously, DICER is an enzyme involved in the cytoplasmic processing and maturation of microRNAs. The use of microRNA target prediction programs (e.g., TargetScan v7.1: www.targetscan.org, mirdb: www.mirdb.org, TarBase v8.0: http://carolina.…”
Section: Resultsmentioning
confidence: 94%
“…Of note, Epithelial-to mesenchymal transition (EMT) is a process in which epithelial cells acquire mesenchymal properties, and increased ability to invade and metastasize [33, 70]. Moreover, studies have now linked EMT with the acquisition of stem-cell characteristics and demonstrated important role of specific claudin proteins in regulating the EMT process, and cancer progression [3, 52]. In this regard, the key role of claudin-1 in regulating the EMT process is well documented.…”
Section: Introductionmentioning
confidence: 99%